Medical Student Experiences of Uncertainty Tolerance Moderators: A Longitudinal Qualitative Study - Stephens, Georgina C.; Sarkar, Mahbub; Lazarus, Michelle D. (Frontiers in Medicine, 2022)
Introduction: Uncertainty tolerance (UT), a construct explicating individuals’ response to perceived uncertainty, is increasingly considered a competency for effective medical practice. Lower UT among physicians is linked with negative outcomes, including less favorable attitudes toward patient-centered care, and increased burnout risk. Despite decades of research, as yet few have engaged methodological approaches aiming to understand the factors that may influence medical students’ UT (so-called moderators). Such knowledge, though, could inform teaching practices for fostering learners’ skills for managing uncertainties. Accordingly, we asked “What factors do medical students in their clinical years perceive as moderating their perceptions of, and responses to, uncertainty?” Methods: We conducted a qualitative study with forty-one medical students in clinical years at an Australian medical school, with data collected throughout 2020. Participants described their experiences of uncertainty through both in-semester reflective diary entries (n=230) and end of semester group or individual semi-structured interviews (n=40). Data were analyzed using a team-based framework analysis approach. Results: Four major themes of UT moderators were identified: 1) Individual factors, 2) Sociocultural factors, 3) Academic factors and 4) Reflective learning. Aspects of individual, sociocultural and academic factors were perceived as having either positive or negative influences on students’ perceptions of uncertainty. By contrast, reflective learning was described as having a predominantly positive influence on students’ perceptions of uncertainty, with students noting learning opportunities and personal growth afforded through uncertain experiences. Conclusions: As healthcare becomes increasingly complex, a future challenge is equipping our medical students with strategies and skills to manage uncertainties. Our study identified multiple moderators of medical students’ UT, key among them being reflective learning. We also identified UT moderators that contemporary and future medical educators may be able to harness in order to develop learner UT as a healthcare graduate attribute, especially through teaching practices such as intellectual candor. Further research is now required to evaluate the impact of proposed educational interventions, and to develop effective assessments of students’ skills for managing clinical uncertainties.